Philosophical Foundations of Holistic Education in the 21st Century - Muhammad Nasir; Muhammad Khairul Rijal; Amie Primarni; Lucas Lima; Singgih Prastawa (International Journal of Educational Narratives, 2024)
The 21st century brings an increasing demand for educational approaches that develop not only intellectual but also emotional, social, and ethical dimensions of learners, positioning holistic education as a relevant framework. Rooted in philosophies that value the interconnectedness of knowledge, self-awareness, and community responsibility, holistic education emphasizes the development of well-rounded individuals prepared to engage with complex global issues. This research aims to explore the philosophical foundations of holistic education, examining key principles from thinkers such as Rousseau, Dewey, and Steiner that support a balanced, learner-centered approach. A qualitative research methodology was used, involving a comprehensive literature review of philosophical texts and educational theory. Analysis focused on identifying core values in holistic education, including the nurturing of emotional intelligence, ethical understanding, and social responsibility. The study also examined modern adaptations of these philosophies in contemporary educational practices, highlighting how traditional philosophies inform current holistic teaching methods. Findings indicate that holistic education effectively addresses the multidimensional needs of learners, promoting critical thinking, empathy, and personal growth. The results reveal that integrating these philosophical principles encourages an inclusive and adaptable educational model that aligns with 21st-century learning objectives. Holistic education thus provides a viable alternative to conventional models focused solely on academic achievement. This study concludes that embracing the philosophical foundations of holistic education can foster a more inclusive, adaptive, and socially responsible approach to learning. Further research is recommended to explore practical applications and the impact of holistic education on diverse learning environments.